At the Grave We Make Our Song*: A Palliative Care Study in Rural Guatemala - Traister, Erin M (East Carolina University, 2016)
Background: Palliative care in Guatemala has received limited attention and research, resulting in an inadequate understanding of the needs of Guatemalans at the end-of-life (EOL). Guatemala ranks at the bottom of the Latin American Association for Palliative Care Index (Pastrana, Torres-Vigil, & DeLima, 2014). Women in the community have been identified as having an important spiritual role during EOL (Malcom, 2003; Miranda, 2007). Purpose: To understand EOL decision making, family involvement, and cultural/spiritual practices of rural Guatemalans. Methods: We conducted interviews with six Guatemalan families and one community leader in Spanish using a structured interview guide. Responses were translated into English and data was interpreted using content analysis. Findings: Relief from Suffering was the over-arching theme found through three support systems: the family, community rezadora, and priest. The family’s role was one of listening, making decisions, and providing love and care for the dying person. The community rezadora, a lay spiritual leader, was called upon to sing prayers and prepare the home altar, comforting the family and community. The priest’s role included the traditional sacraments. Physicians had some presence in EOL care, whereas nurses had no presence. Conclusions: International EOL training programs with Guatemalan nurses and families may be a valuable next step. Palliative nursing care in the US should consider incorporating cultural partners, such as the community rezadora. Further research on the role of rezadoras in the US would increase understanding of Guatemalan beliefs and practices. References Malcolm, T. (2003). Creating sacred space. National Catholic Reporter. Retrieved from http://natcath.org/NCR_Online/archives2/2003d/111403/111403k.htm Miranda, I. (2007). Faith formation with Hispanic/Latino families. Lifelong Faith, 1(2), 21-29. Retrieved from http://www.lifelongfaith.com/uploads/5/1/6/4/5164069/lifelong_faith_journal_1.2.pdf Pastrana,T., Torres-Vigil, I., & DeLima, L. (2014). Palliative care development in Latin America: an analysis using macro indicators. Palliative Medicine, 28(10), 1231-1238. Retrieved from http://www.ncbi.nlm.nih.gov/pubmed/24925578
Keywords: Guatemala; palliative care; end-of-life